Superexpressão da Stress Inducible Protein 1 (STI1) em camundongos: um novo alvo molecular com função cardioprotetora - Katyana Kaline Silva Ferreira (2023)
STI1 (Stress inducible protein 1) is an important co-chaperone in protein quality control, and protein homeostasis. Recently, our research group found that STI1 expression is reduced in the hearts of heart failure patients. Furthermore, it plays a relevant role in cardiac hypertrophy and injury in mice with reduced STI1 expression, making them more susceptible to cardiac injury after hypertrophic stress. Could STI1 overexpression play a protective role in the heart? As the main goal of this work, we propose to investigate the consequences of STI1 overexpression for cardiac function in mice at baseline and after hypertrophic stress induced by adrenergic hyperactivation caused by isoproterenol. For this, we used wild-type mice (WT) and transgenic mice with global overexpression of STI1 (STI1-TgA), aged from 10-12 weeks. Initially, we analyzed baseline development and cardiac function by evaluating structural, morphological, and functional characteristics of the heart by immunofluorescence, cellular morphometry, and cardiomyocyte (CMs) contractility. Besides, we performed a cardiac proteomic profile of STI1-TgA mice. Finally, we induced hypertrophic stress by injecting the β-adrenergic agonist isoproterenol (ISO: i.p. 20mg/Kg/day for 7 days). Control mice were treated with saline (0.9% NaCl). On the eighth day, we performed echocardiography experiments and then the hearts were collected for immunofluorescence, cell morphometry, western blotting, qPCR, and contractility and Ca2+ transient (Fluo-4/AM) experiments on CMs. The baseline characterization of the STI1-TgA transgenic mice confirmed the elevation of STI1 expression in the heart and cardiac growth similar to control (WT) as assessed by the HW/TL ratio and CM morphometry. Interestingly, STI1-TgA mice showed an increase in contractile function of CMs, which was explained by an increase in the Ca2+ transient amplitude. Our proteomic analysis identified that STI1-TgA animals have alterations in the baseline expression of proteins involved in hypertrophic signaling, cellular response to stress, RNA metabolism, protein quality control, and protein degradation, indicating that these animals display cardiac adaptations to stress. Hypertrophic stress caused by ISO did not induce significant hypertrophy in STI1-TgA mice (~16%), different from what occurred in WT/ISO mice which developed cardiac hypertrophy (~35%) and presented enlarged CMs. Besides, WT/ISO also showed increased mRNA levels for cardiac stress markers, such as Myh7 and ANP. When we evaluated the CMs contractility and Ca2+ transient amplitude, both were increased in WT/ISO, as well as, the similar to STI1-TgA/ISO. When evaluating the collagen deposition and fibrosis induced by ISO, only the WT/ISO group showed an increase in collagen III levels in the cardiac tissue. When we evaluated the activation of the antioxidant response, STI1-TgA/ISO mice expressed 4x more the NRF2 transcription factor, suggesting an improved antioxidant response. Taken together, our data show that STI1 overexpression provides a framework for cardiac adaptation to stress, which in response to adrenergic hyperactivation protects the heart from cardiac ISO-induced injury, improving contractile function, and antioxidant response. Thereby, we conclude that STI1 overexpression plays a cardioprotective role and may become a relevant therapeutic target in the treatment of heart diseases.